Pengaruh Skeptisisme Profesional, Independensi, Dan Pengalaman Auditor Terhadap Kemampuan Auditor Mendeteksi Fraud - Tio Revi Suganda; Sri Ambarwati; Tri Astuti (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2018)
Auditing is a process that aims to give an opinion on the fairness of the financial statements. In addition to give an opinion on the fairness of the financial statements, the auditor is also responsible for reporting the findings of fraudulent financial statements, if any. This study aimed to examine the effect of professional skepticism, independency, and experience towards fraud detection. This study was conducted on Kantor Badan Pengawasan Keuangan dan Pembangunan (BPKP). The sample that used are 45 auditors. The sample in this research was determined by purpossive sampling method. Data were collected using questionaires. Data analysis technique used is multiple linear regression analysis. Based on the analysis found that professional skepticism has a positive and significant effect on fraud detection, auditor independence has a positive and significant effect on fraud detection, and the auditor’s experiences have a positive and significant effect on fraud detection.